Effect of BCG vaccination on risk of Mycobacterium tuberculosis infection in children with household tuberculosis contact: a prospective community-based study - (:unkn) unknown (ELSEVIER SCIENCE INC, 2005)
Background Little is known about factors that affect the risk of acquiring infection in children exposed to Mycobacterium tuberculosis. The effect of BCG vaccination has been difficult to ascertain because the tuberculin skin test (TST), until recently the only method for detecting M tuberculosis infection, does not reliably distinguish between tuberculosis infection and BCG vaccination. Methods We investigated risk factors for tuberculosis infection in 979 child household contacts of 414 adult index patients withildren were aged up to 16 years (median 7, IQR 3-11) and 770 of 979 (79%) had a BCG scar. A T-cell-based enzyme-linked immunospot assay (ELISpot), sputum smear-positive pulmonary tuberculosis in Istanbul, Turkey. Chwhich is not confounded by BCG vaccination, and TST were used to assess infection. Independent risk factors for infection were identified through multivariate analysis. Findings Amount of tuberculosis exposure within the household and age (a marker of tuberculosis exposure outside the household) were strongly associated with likelihood of infection as measured by both TST and ELISpot. ELISpot also identified absence of BCG scar as an independent risk factor for infection in tuberculosis-exposed children; BCG-vaccinated children had an odds ratio of 0.60 (95% Cl 0.43-0.83, p=0.003) for tuberculosis infection, compared with unvaccinated children. Interpretation Contrary to the prevailing theory that BCG vaccination protects only against tuberculosis disease, our results suggest that the vaccine also protects against tuberculosis infection. This finding has important implications for our understanding of the biology of tuberculosis infection and development of improved tuberculosis vaccines.
Keywords: BACILLUS-CALMETTE-GUERIN; VACCINIA VIRUS ANKARA; SKIN-TEST; BOVIS BCG; T-CELLS; METAANALYSIS; EFFICACY; GAMMA; ENUMERATION; POPULATION